The impact of cultivar development and cultural practices on Louisiana rice yield. Issue 1 (21st January 2022) - Kennedy, P. Lynn; Schmitz, Andrew; Linscombe, Steve; Zhang, Fangyi
Abstract: This analysis investigates the impact of cultivar development and cultural practices on Louisiana rice ( Oryza sativa L.) yield growth using the Chow test (Chow, 1960) in combination with regression analysis. The analysis examines the 1895–2019 period, and uses four scenarios in which one, two, three, and four subperiods show varying rates of rice yield growth in Louisiana. There has been a significant increase in Louisiana rice yields over time. However, the growth in yields for some of the subperiods is greater than for others. Our results of significant rice yield increase over time correspond with events such as the establishment of Louisiana's Foundation Seed Program, the release of the Magnolia rice cultivar, and increased mechanization. Core Ideas: Louisiana rice yields have increased through cultivar development and cultural practices. This dual relationship is important when assessing return to research investment. Rice cultivar development is important but is not the sole factor influencing productivity.